1988
DOI: 10.1210/jcem-67-6-1186
|View full text |Cite
|
Sign up to set email alerts
|

Arginine Stimulates Growth Hormone Secretion by Suppressing Endogenous Somatostatin Secretion*

Abstract: To determine how arginine (Arg) stimulates GH secretion, we investigated its interaction with GHRH in vivo and in vitro. Six normal men were studied on four occasions: 1) Arg-TRH, 30 g arginine were administered in 500 mL saline in 30 min, followed by an injection of 200 micrograms TRH; 2) GHRH-Arg-TRH, 100 micrograms GHRH-(1-44) were given iv as a bolus immediately before the Arg infusion, followed by 200 micrograms TRH, iv; 3) GHRH test, 100 micrograms GHRH were given as an iv bolus; and 4) TRH test, 200 mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
94
3

Year Published

1990
1990
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 324 publications
(109 citation statements)
references
References 20 publications
(21 reference statements)
7
94
3
Order By: Relevance
“…Campbell et al (2004) reported that it is well documented that the infusion of arginine stimulates growth hormone secretion from the anterior pituitary. This increase in growth hormone secretion has been attributed to the suppression of endogenous somatostatin secretion (Alba-Roth et al, 1988). Darras et al (1990;1992) indicated that during embryonic growth, liver cells are capable of responding to the growth hormone by converting T4 to T3 and decreasing type III iodothyronine deiodinase.…”
Section: Resultsmentioning
confidence: 99%
“…Campbell et al (2004) reported that it is well documented that the infusion of arginine stimulates growth hormone secretion from the anterior pituitary. This increase in growth hormone secretion has been attributed to the suppression of endogenous somatostatin secretion (Alba-Roth et al, 1988). Darras et al (1990;1992) indicated that during embryonic growth, liver cells are capable of responding to the growth hormone by converting T4 to T3 and decreasing type III iodothyronine deiodinase.…”
Section: Resultsmentioning
confidence: 99%
“…This is believed to be due to their somatostatinergic hypertone [35]. ARG-induced GH release is probably mediated by a decrease in the somatostatinergic tone as demonstrated indirectly by the use of cholinesterase inhibitors in man [1,18,20] and pigs [10].…”
mentioning
confidence: 99%
“…Insulin-induced hypoglycemia and arginine stimulate GH secretion by suppressing endogenous somatostatin secretion in the hypothalamus [14,15]. GHRP-2 is a potent synthetic GH secretagogue, which acts on a specific receptor at the hypothalamic arcuate nucleus-median eminence to potentiate GH-releasing activity [16,17].…”
Section: Discussionmentioning
confidence: 99%